Acidic preconditioning improves the proangiogenic responses of endothelial colony forming cells - Mena, Hebe Agustina (2014)
Objective: Acidosis is present in several pathological conditions where vasculogenesis takes place including ischemia, tumor growth and wound healing. We have previously demonstrated that acidosis induces human CD34+ cell apoptosis. Considering that endothelial colony-forming cells (ECFC) are a subpopulation of CD34+ cells and key players in vasculogenesis, in the present study we investigated the effect of acidosis on the survival and functionality of ECFC. Approach and results: Endothelial colony-forming cells obtained by differentiation of human cord blood CD34+ cells in endothelial growth medium-2 for 14–21 days were exposed at pH 7.4, 7.0 or 6.6. We found that acidosis failed to induce ECFC apoptosis and, although an early reduction in proliferation, chemotaxis, wound healing and capillary-like tubule formation was observed, once the medium pH was restored to 7.4, ECFC proliferation and tubulogenesis were augmented. Stromal cell derived factor-1 (SDF1)-driven migration and chemokine receptor type 4 surface expression were also increased. The maximal proangiogenic effect exerted by acidic preconditioning was observed after 6 h at pH 6.6. Furthermore, preconditioned ECFC showed an increased ability to promote tissue revascularization in a murine model of hind limb ischemia. Immunoblotting assays showed that acidosis activated AKT and ERK1/2 and inhibited p38 pathways. Proliferation rises triggered by acidic preconditioning were no longer observed after AKT or ERK1/2 inhibition, whereas p38 suppression not only mimicked but also potentiated the effect of acidosis on ECFC tubule formation abilities. Conclusions: These results demonstrate that acidic preconditioning greatly increases ECFC-mediated angiogenesis in vitro including ECFC proliferation, tubulogenesis and SDF1-driven chemotaxis and is a positive regulator of microvessel formation in vivo.